Kaolin-carbon adsorbents for carotene removal of red palm oil - Hussein, Mohd Zobir; Kuang, Dzulkefly; Zainal, Zulkarnain; Teck, Tan Kian (Academic Press, 2001)
Kaolin-carbon adsorbents were prepared with and without sulfuric acid pretreatment followed by activation-carbonization at 500°C. The total surface area of the resulting kaolin-carbon adsorbents was found to be decreased with the increase in kaolin loading. Sulfuric acid pretreatment of the precursor prior to the carbonization-activation processes resulted in the enhancement of total surface area but reduced the micropore surface area of the resulting adsorbents. At the same time, this improved carotene adsorption capacity from red palm oil. However, recovery of carotene from the carotene-adsorbed adsorbent is only improved when the acid pretreatment of the precursor was done at a high loading percentage of activated carbon. Similarly, the peroxide value (PV) increased. A maximum removal of carotene from red palm oil was obtained at 20% kaolin loading for both adsorbents prepared with and without sulfuric acid pretreatment with about 45 and 65% carotene removal, respectively, from a 30-ppm solution. This indicates that pretreatment with sulfuric acid, prior to the activation-carbonization process, increased the carotene uptake by the resulting adsorbent. However, a further increase in the kaolin loading resulted in the decrease of carotene removal. About 3-4% of carotene adsorbed can be recovered from both types of adsorbents under optimum condition, in which the percentage recovered decreased with the increase in kaolin loading. On the other hand, the PV increased with kaolin loading at around 54-64 mEq/kg for both types of adsorbents. It was also found that carotene uptake by the adsorbents is high if the adsorbent contains a high percentage of activated carbon. Similarly, carotene recovery is high and less oxidation can be observed, as indicated by the lower PV value. © 2001 Academic Press.